Costs and Benefits of Bilingual Education in Guatemala : A partial Analysis - Patrinos, H. A.; Velez, E. (2012)
The benefits of bilingual education for a disadvantaged indigenous population as an investment in human capital are significant. Students of bilingual schools in Guatemala have higher attendance and promotion rates, and lower repetition and dropout rates. Bilingual students receive higher scores on all subject matters, including mastery of Spanish. The efficiency of bilingual education is confirmed by a crude cost-benefit exercise. A shift to bilingual schooling would result in considerable cost savings because of reduced repetition. The higher quality of education generating higher promotion rates will help students complete primary education and will substantially increase completion rates at low cost. The costs saving due to bilingual education is estimated at $5 million, equal to the cost of primary education for 100,000 students. (C) 2009 Elsevier Ltd. All rights reserved.